Evaluacion quimico-toxicologica de SO2 en el aire del Valle del Colca - Lizano G., Jesús (1999)
The concentrations of the Dióxido of sulfur (SO2) like pollutant are studing in a specific zone of the Valley of th e Colca - Arequipa, being the issuing principal of contaminaüon the Sabancaya Volcano. This volcano introduces signs of activity, the one which apparent for earthquake movements and clouds of smoke, being precisely these those that, between other, they have a load in sulphurous gases and SO 2Like secondary fountain of contamination is the automobile park and the industrial sector which goin increment in proportion to old signs of economical-social progress are generated in the Valley.It for the determination of concentrations was utilized the Method of West and Gaecke, taking 162 patterns of air in three analitical areas: Chivay, Maca and Ichupampa, represented by the towns of statements names. The outputs demonstrate the existence of a relatively tall concentration of the investigated toxic, the one which to their time would occasion toxic bothers to the health of the population.The work analyzes the gotten outputs, estadistical and eomparatively; like it study the problems that could have for the life as much animal as vegetable of the zone, and very especially; the effects that could introduce in the due human beings to exposition on the pollutant.